Comparison of caries diagnostic modalities: A clinical study in 40 subjects - Mansour, Stephanie; Ajdaharian, Janet; Nabelsi, Tasneem; Chan, Gregory; Wilder-Smith, Petra (Lasers in surgery and medicine, 2016)
Background and Objectives Few studies have been published that evaluate the usefulness of different caries‐ diagnostic modalities in general dental practice. The goal of this study was to compare the results of screening for coronal dental caries in a general dental practice using clinical observations, radiographs, laser fluorescence (DIAGNOdent™) (LF), and optical coherence tomography (OCT). Diagnostic agreement between OCT and LF versus standard clinical techniques for detecting caries was determined in 40 subjects. Study Designs/Materials and Methods Forty patients with >1 coronal carious lesion as determined by prescreening using clinical examination and radiographs were enrolled in this study. Subjects with gross caries were excluded. Subsequently each patient underwent a full detailed dental examination by an experienced clinician, using visual examination and radiographs according to standard clinical practice. The coronal surfaces of a total of 932 teeth were examined and charted. Teeth were then photographed, rediagnosed using the LF system, and imaged using OCT. Two blinded pre‐standardized examiners reviewed radiographic and OCT images and assigned caries status. Results Based on manufacturer's cutoff values, sensitivity and specificity for coronal caries using LF technique (i) on unaltered tooth surfaces were 73.7% and 94.1%, respectively and (ii) in previously restored or sealed teeth, they were 19.2% and 95.8%, respectively. LF technique was unable to assess tissue health underneath sealants and restorations. Clinician agreement (kappa [k]) regarding caries diagnosis using OCT imaging was overall 0.834 (SE = 0.034). Sensitivity and specificity for caries using OCT technique (i) on unaltered tooth surfaces approximated 74.1% and 95.7%, respectively and, (ii) in previously restored or sealed teeth, they approximated 76.0% and 95.6%, respectively. Although OCT was able to detect lesions beneath many resin restorations and sealants, results varied considerably between materials. OCT imaging was unable to detect caries when caries was >2 mm below the tooth surface. Conclusion These findings support the usefulness of LF for primary caries detection, and the clinical utility of OCT for early caries detection and monitoring under dental resin restorations and sealants. Lasers Surg. Med. 48:924–928, 2016. © 2016 Wiley Periodicals, Inc.